Impelemntasi Green Building pada Poryek Konstruksi di Manokwari dengan Pendekatan Lean Construction - Natalia E Safkaur (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
The construction sector significantly contributes to global energy consumption and carbon emissions, necessitating integrated strategies that combine operational efficiency and environmental sustainability. This study develops a conceptual Lean–Green integration model for construction projects in Manokwari through a Systematic Literature Review following the PRISMA protocol. The analysis synthesizes empirical findings published between 2018 and 2026 to examine the causal relationships between Lean Construction practices and Green Building performance indicators. The results indicate that Lean–Green integration potentially reduces material waste by 15–35%, decreases project costs by 10–20%, and improves operational energy efficiency by up to 30%. The proposed input–process–output framework identifies managerial commitment, workforce capability, regulatory support, and digital technology integration as critical determinants of successful implementation. The discussion highlights organizational culture, risk management, supply chain integration, and BIM-based digitalization as strategic enablers in peripheral regions with logistical constraints.